Analisis Perbandingan antara Pengenaan Pajak Penjualan dan PPN akibat Perubahan PKP2B menjadi IUPK dan Adanya UU Cipta Kerja - Shahnaz Arianne Amirah; Sri Trisnaningsih (Universitas Batanghari Jambi, 2022)
Generation I PKP2B contractors are subject to a special tax, namely sales tax which should generally be subject to value added tax. There are several objectives of this research including deeply analize about the imposition of value sales tax on PKP2B contractors; Deeply analize about the imposition of value added tax on IUPK contractors; and To analyze the impact of the Job Creation Act on Coal Value Added Tax.This kind of research is qualitative research. This Research have some conclusion, include that it is more economical in paying taxes if the value added tax is applied after coal becomes taxable goods rather than sales tax; The existence of the Job Creation Law which regulates that coal is subject to value added tax is also more profitable for companies and the government; there was a finding that when coal was initially taxed according to the work copyright law, it was in November 2021, but in reality it had not been implemented in November 2021 for incoming transactions, while issuing tax invoices with code 010 for outgoing transactions, namely coal sales due to continuing to adhere to PKP2B and is subject to sales tax, although the contract has changed in January 2022, it will not be enforced until April 18, 2022 due to waiting for Government Regulation number 15 of 2022